Enhanced ethanol production from lignocellulosic hydrolysates by inhibiting the hydrogen synthesis in Thermoanaerobacterium aotearoense SCUT27(Δldh). Issue 10 (25th July 2019) - Fu, Hongxin; Yang, Xitong; Qu, Chunyun; Li, Yang; Wang, Jufang
Abstract: BACKGROUND: Thermophilic anaerobic bacteria have gained increased interest as a desirable biological catalyst for bioethanol production from lignocellulosic biomass. However, by‐products such as lactic acid, acetic acid and hydrogen (H2 ) not only lead to low ethanol yield but also increase the difficulty of ethanol purification. Considering that ethanol production is dependent on the supply of NADH, blocking or inhibiting lactic acid (by knocking out ldh ) and H2 formation should be a reliable strategy to further increase the ethanol production. RESULTS: Comparative genome analysis indicated that three hydrogenase gene clusters ( hyd, ech and hfs ) were identified in Thermoanaerobacterium aotearoense SCUT27, and they were proved to be related to H2 production by gene knockout. Deletion of hyd or ech in SCUT27(Δ ldh ) showed a decrease in substrate consumption and ethanol production, while hfsB gene knockout resulted in significant improvement in overall fermentation performance. Compared with SCUT27(Δ ldh ), the ethanol concentration, yield and productivity of SCUT27(Δ ldh /Δ hfsB ) were increased from 25.15 ± 0.45 g L −1, 0.33 ± 0.01 g g −1 and 0.30 ± 0.01 g L −1 h −1 to 39.64 ± 0.16 g L −1, 0.36 ± 0.00 g g −1 and 0.41 ± 0.01 g L −1 h −1 respectively using glucose in fed‐batch fermentation. The enhanced ethanol production was due to the increased NADH supply and alcohol dehydrogenase activity. Finally, the feasibility of ethanol production by SCUT27(Δ ldh /Δ hfsB ) from hydrolysates of soybean hull, wheat straw, corn cob and corn straw was demonstrated. CONCLUSION: Knocking out the ldh and hfsB in SCUT27 is an efficient strategy for diverting carbon flux and NADH towards ethanol production, and the resulting strain SCUT27(Δ ldh /Δ hfsB ) has great potential in the production of ethanol from lignocellulosic hydrolysates. © 2019 Society of Chemical Industry